2021
DOI: 10.1021/acsami.1c19471
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Color Elastomers Combining Structural, Dye, and Background Colors

Abstract: Organisms that alter body color undergo color change in response to environmental variations and stimuli by combining chromatophores that develop colors by various mechanisms. Inspired by their body color changes, we can develop sensors and optical materials that change colors in response to multiple stimuli, such as mechanical and light stimuli. In this study, we report on bioinspired composite elastomers that exhibit various color changes as the pigment color, structural color, and background color change. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…To show the electrochromic behavior of the H-SiO 2 /WO 3 PC film further clearly, the reflection spectra of the original film, after the different electric field was applied for 5 s and after −5 V voltage was applied for different times, were recorded in Figure c. The reflection spectrum of the original film peaked at 583 nm, while it blue-shifted about 60 to 524 nm after −5 V voltage was applied for 5 s. Meanwhile, an obvious decrease in reflectance also occurred, because of the decreased contrast of refractive indices , and the increased absorption of partial wavelengths (<500 nm) for the H-SiO 2 /WO 3 PC films. In addition, the blue-shifted distance (Δλ) of the reflected wavelength gradually increases with voltage change from −0.25 to −5 V. When the voltage is <0.25 V, Δλ of the sample is small, while when the voltage is >5 V, Δλ of the sample becomes nearly constant.…”
Section: Resultsmentioning
confidence: 99%
“…To show the electrochromic behavior of the H-SiO 2 /WO 3 PC film further clearly, the reflection spectra of the original film, after the different electric field was applied for 5 s and after −5 V voltage was applied for different times, were recorded in Figure c. The reflection spectrum of the original film peaked at 583 nm, while it blue-shifted about 60 to 524 nm after −5 V voltage was applied for 5 s. Meanwhile, an obvious decrease in reflectance also occurred, because of the decreased contrast of refractive indices , and the increased absorption of partial wavelengths (<500 nm) for the H-SiO 2 /WO 3 PC films. In addition, the blue-shifted distance (Δλ) of the reflected wavelength gradually increases with voltage change from −0.25 to −5 V. When the voltage is <0.25 V, Δλ of the sample is small, while when the voltage is >5 V, Δλ of the sample becomes nearly constant.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, the complex photonic structures found in color-changing animals such as chamaleons and cephalopods have inspired the design of high-performance mechanochromic systems, [116] by generating high-refractive index contrast PhCs, [117] stiffness gradients, [118] and combining structural color and molecular light absorption. [119,120] Remarkably, Wu et al reported a mechanochromic and thermochromic material mimicking the chameleon skin based on periodic arrays of colloidal particles with high-refractive index contrast, which blue-shifted more than 200 nm by a 20% compression or a temperature increase from 30 to 55 °C. [117] As a step forward, Wang et al developed a bioinspired structural color patch for biomedical applications based on a hydrogel inverse opal with anisotropic surface adhesion and self-reporting capability [121] (Figure 5f).…”
Section: Mechanochromic Systems Based On Other Nanoplasmonic Interact...mentioning
confidence: 99%
“…[ 4 , 5 ] Therefore, it is doubtless that a bionic mechanochromic material, with mechanochromism mechanisms like the cephalopod, can achieve richer optical properties and carry more information. [ 6 , 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Therefore, it is doubtless that a bionic mechanochromic material, with mechanochromism mechanisms like the cephalopod, can achieve richer optical properties and carry more information. [6,7] Recently, some biomimetic mechanochromic materials based on cholesteric liquid crystals (CLCs) have been reported. [8][9][10][11] Kizhakidathazhath et al reported a mechanochromic cholesteric liquid crystals elastomer (CLCE) film using two-stage thiolacrylate Michael addition and photopolymerization reaction that resulted in a robust, rapid, and reversible mechanochromic response to CLCE film stretching.…”
Section: Introductionmentioning
confidence: 99%